Le plan Stoica et les relations entre la Roumanie et la Grèce au tournant de la guerre froide (1957) - Irina Gridan (Cahiers Balkaniques)
The Cold War experienced a turning point with the adoption by the USSR of the doctrine of the peaceful coexistence. However, had this ideological shift had consequences on the relationship between Romania and Greece, each one being in the respective shadow of the USSR and of the United States? The aim of this article is to consider the specificities and the similarities of the roles of these two countries in geopolitical structures that transcend them. Hence, it questions the stability of the cold war borders: may the blocs have a variable geography? From the Stoica plan of balkanic denuclearization that Bucharest proposed to Athens in September 1957, the study analyses the goals of the Romanian‑Greek rapprochement, its limits and its benefits in terms of propaganda. In doing so, it shows that for the Romanian and the Sovietic sides, the Stoica plan allows a peripheral destabilization of the Western camp; for the Greek side, it allows a kind of blackmail around the participation to the Atlantic alliance. Nevertheless, the global logic of Cold War finally triumphs over the regional logic of Balkan cooperation.